Innovative Learning Environments : The Role of Energy-Efficient Investments in Russian Preschool Education Facilities (A Case Study of the Khanty-Mansyisk Region) - Shmis, Tigran; Chugunov, Dmitry; Ustinova, Maria; Kotnik, Jure (World Bank, Washington, DC, 2019)
This paper discusses an example of an early childhood development facility intervention in the Khanty-Mansyisk region of the Russian Federation and its potential to produce efficiency gains in the region and the country overall. The government of the region is introducing changes to the built environment of its early childhood development centers. The proposed new design is based on the concept of the learning environment as a third teacher. The smaller footprint of the new buildings will increase the amount of active space per child, and the new design will include energy efficiency measures. The economic impact of these measures will reduce operating costs throughout the lifecycle of the building and provide strong evidence to education policy makers in the rest of the region and the country as a whole in favor of child-centered, healthy, and energy efficient early childhood development infrastructure.